Sistem Pendukung Keputusan Pemilihan Cafe di Yogyakarta dengan Menggunakan Metode Simple Additive Weighting (SAW) - Muhammad Nur Hendra Alvianto; Shoffan Saifullah (Journal of Innovation Information Technology and Application (JINITA), 2020)
The development of the culinary business in Indonesia is developing very fast, one of which is the business of blending coffee drinks or commonly called café. This business is growing very fast, and there are many variants of concoctions in Indonesia, one of which is located in Yogyakarta. The many cafes that open in Yogyakarta have an impact on students' confusion to choose which recommendations are most comfortable for students to use as a place of discussion or place of study. Besides, usually, newcomers, especially students who have just arrived in Yogyakarta, tour the city in search of places that are comfortable to use to unwind. In this study, conducting interviews with 10 respondents, the results were processed and processed using the Simple Additive Weighting (SAW) method. SAW is one of the methods used in making decisions. This method is used to determine the best café recommendations in Yogyakarta. These café recommendations are expected to be in accordance with what students are looking for by taking into account café facilities, café locations, and the price range offered. The calculation result of the SAW method in the recommended cafe in Yogyakarta is Cafe B, with a yield of 9.4, which is the highest value. Based on the results of these calculations and analysis, the facilities provided by the café are the main attraction for visitors. Besides, the use of the SAW method can also provide the best café recommendations as initial recommendations for new students in Yogyakarta